Moda e os uniformes escolares: aspectos históricos do fardamento escolar no Ceará - Silveira, Eveline Maria de Azevedo (2016)
This research aimed to understand how it developed the use of school uniform in Brazil and especially in the state of Ceará. For that they were conducted historical studies, bibliographic and iconographic on the use of school uniforms from the midnineteenth century to the end of the 70s of the twentieth century. The research aimed to address how the use of the school uniform was established in Ceará during the 1940s to the late 1970. The choice of this period was mainly, for we can interview former students who were students from the 1940s During the research it was also possible to understand which were the uniform use of symbols both for students and for society in general. For a better understanding of the subject they were chosen two schools that were part of the history of education in the State of Ceará: the Ceará Lyceum College and Normal School of Ceará, both public maintained by the State Government. Throughout the history of these schools, interviews with former students of the time and conversations with today's employees can know as was the story of the school uniform during the set period. This work revealed historical aspects of school uniforms in Ceará relating to fashion and uniforms cearenses schools, performing also brief history of local education.